Testing effects of Lorentz invariance violation in the propagation of astroparticles with the Pierre Auger Observatory - Binet, V. (2022)
Fil: Fil: Binet, V. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física de Rosario (IFIR-CONICET); Argentina.